Analyses of melatonin, cytokines, and sleep in chronic renal failure - Pinto, Aline Rodrigues [UNESP]; Silva, Nathani Cristina da [UNESP]; Pinato, Luciana [UNESP] (Springer, 2016)
Inflammation and oxidative stress are involved in the process of chronic renal failure (CRF). CRF patients show indication of sleep disturbances, and the melatonin rhythm, which modulates sleep, is abnormal in these patients; however, it is still unclear whether inflammation could be related to the blockage of melatonin production and sleep disturbances in this population. The aim of this study was to characterize and correlate sleep, the melatonin rhythm, and the levels of the inflammatory cytokines tumor necrosis factor (TNF) and interleukin (IL)-6 in patients with CRF and controls. Sleep was evaluated by the Sleep Quality Index Pittsburgh (PSQI) questionnaire, and melatonin and cytokine contents in saliva and blood samples, respectively, were analyzed by ELISA. The CRF group scored higher on the global PSQI, which indicates a lower sleep quality and a higher prevalence of sleep disorders, than the control group. The CRF individuals also showed lower melatonin content than the control groups, both during the day and at night, and lacked rhythmicity in melatonin production. The CRF group also showed higher contents of TNF and IL-6 than the control group and a negative correlation between TNF and melatonin content. These results suggest that the sleep disorders observed in the CRF group were probably related to the low production of melatonin observed in this population. The high level of TNF, as previously demonstrated in other pathologies, is probably involved in this blockage of melatonin production in CRF.
Keywords: Inflammation; Biological rhythms; Sleep quality; Immune-pineal axis; Behavior